Sub-national variations in general service readiness of primary health care facilities in Ghana: Health policy and equity implications towards the attainment of Universal Health Coverage - Martin Ayanore; Robert Asampong; James Akazili; John Koku Awoonor-Williams; Patricia Akweongo (PLoS ONE, 2022)
Background Service availability and readiness are critical for the delivery of quality and essential health care services. In Ghana, there is paucity of literature that describes general service readiness (GSR) of primary health care (PHC) facilities within the national context. This study therefore assessed the GSR of PHC facilities in Ghana to provide evidence to inform heath policy and drive action towards reducing health inequities. Methods We analysed data from 140 Service Delivery Points (SDPs) that were part of the Performance Monitoring and Accountability 2020 survey (PMA2020). GSR was computed using the Service Availability and Readiness Assessment (SARA) manual based on four out of five components. Descriptive statistics were computed for both continuous and categorical variables. A multivariable binary logistic regression model was fitted to assess predictors of scoring above the mean GSR. Analyses were performed using Stata version 16.0. Significance level was set at p<0.05. Results The average GSR index of SDPs in this study was 83.4%. Specifically, the mean GSR of hospitals was 92.8%, whereas health centres/clinics and CHPS compounds scored 78.0% and 64.3% respectively. The least average scores were observed in the essential medicines and standard precautions for infection prevention categories. We found significant sub-national, urban-rural and facility-related disparities in GSR. Compared to the Greater Accra Region, SDPs in the Eastern, Western, Upper East and Upper West Regions had significantly reduced odds of scoring above the overall GSR. Majority of SDPs with GSR below the average were from rural areas. Conclusion Overall, GSR among SDPs is appreciable as compared to other settings. The study highlights the existence of regional, urban-rural and facility-related differences in GSR of SDPs. The reality of health inequities has crucial policy implications which need to be addressed urgently to fast-track progress towards the achievement of the SDGs and UHC targets by 2030.